The Influence of Competence and Motivation on Performance and Impact on Reward among Nurses (Universitas Muhammadiyah Yogyakarta, 2025)
Nurses’ performance is a key determinant of the success and quality of hospital services. Based on data from Dinas Kesehatan Sumatera Utara (2024), the performance targets and realizations of RSUD dr. Thomsen has not yet achieved the expected targets for health service performance indicators in 2022 (64.58%), 2023 (92.34%), and 2024 (94.47%). Similarly, the hospital's performance score was in 2022, (70%), in 2023, (80%) and in 2024 (82%). A pre-survey of 30 nurses regarding factors suspected of influencing performance revealed the lowest average scores: competence (2.72), motivation (2.63), and rewards (3.25) (Likert scale 1–5). This study aims to analyze the influence of competence and motivation on performance and their impact on rewards. The research method used a quantitative approach with 175 respondents and path analysis. The results showed that competence and motivation significantly affected performance, partially and simultaneously. Performance also significantly affected rewards. These findings indicated the importance of improving nurses' competence and motivation in efforts to improve nurse performance and rewards in hospitals. This study provides practical contributions to hospital human resource management policies, particularly in strengthening a transparent and fair performance-based reward system. The findings also enrich the literature by demonstrating the simultaneous relationship between competence, motivation, performance, and rewards in the context of regional hospitals, which has been rarely explored in previous studies.